The Modern Poets (Ṭabaqāt al-shuʿarāʾ al-muḥdathīn) - al-Muʿtazz, Abd Allāh ibn, (Handbook of Oriental Studies. Section 1 The Near and Middle East ;, 2026)
The Modern Poets is the first complete translation into any language of an important and entertaining anthology compiled by the famous Arabic poet and Abbasid prince, ʿAbd Allāh ibn al-Muʿtazz, who reigned as Caliph in Baghdad for one day in AD 908, before being killed the next day. It contains sections on 132 8th- and 9th-century Arabic poets, famous and obscure ones, quoting poems of many kinds: praise poems, love poems, wine poems, elegies, vicious lampoons, and jesting epigrams, with many anecdotes. The translation is richly annotated, preceded by an introduction, and provided with indexes. The book offers access to a central text in Arabic literary history and a compelling window into early Abbasid culture.